Three-dimensional analysis of turbulent twin-swirling jets onto a heated rectangular prism in a channel - Gur, Muhammed; Öztop, Hakan Fehmi; Biswas, Nirmalendu; Selimefendigil, Fatih (Emerald Group Publishing Ltd, 2025)
PurposeThe purpose of this study is to investigate the impact of swirling jet flow on the cooling performance of a heated rectangular prism placed within a channel. The primary aim is to explore the influence of varying aspect ratios (AR) of the prism and different fluid Reynolds numbers (Re) on the cooling efficiency.Design/methodology/approachThe numerical analysis is performed using a finite volume-based solver, which incorporates the large eddy simulations (LES) turbulence model. The setup consists of twin 45 degrees swirling jets directed at isothermally heated bodies, with water used as the cooling medium. The rectangular prism is oriented perpendicularly to the channel flow direction, positioned one unit distance from the inlet. This study examines three distinct aspect ratios (AR = 0.5, 1 and 1.5) and a range of Reynolds numbers (6000 = Re = 20000).FindingsThe results indicate that cooling efficiency improves as the aspect ratio decreases and the Reynolds number increases. Higher Reynolds numbers enhance jet impingement and turbulent mixing, which are crucial for efficient heat transfer. Conversely, lower Reynolds numbers lead to diminished impingement and reduced cooling efficiency. Increasing the Reynolds number from 6000 to 20000 elevates the average Nusselt number by 35% (for AR = 0.5) and up to 45% (for AR = 1.5). It was observed that lower aspect ratios produce superior cooling effects due to intensified localized jet interactions.Originality/valueThis research significantly contributes to the fields of fluid dynamics and thermal engineering by elucidating the influence of swirling jet flows on the cooling of heated surfaces. The findings offer valuable insights for optimizing the design and performance of cooling systems across various industrial applications.
Keywords: Swirling jet; Cooling; Aspect ratio; Reynolds number; Large eddy simulations (LES)